Determinants of male involvement in maternal healthcare services in southwest Nigeria. (2nd January 2021) - Olajubu, Aanuoluwapo O; Ayamolowo, Sunday J; Okiti, Oluwatosin A; Olajubu, Temitope O; Adeyeye, Olajumoke; Olowokere, Adekemi E
Abstract : Background/Aims: In Nigeria, women's partners are often excluded from taking part in maternal healthcare, as a result of sociocultural norms. However, the involvement of male partners in maternal healthcare services has the potential to improve maternal health outcomes. This study examined factors associated with male involvement in maternal healthcare services in Ife Central, Osun State, Nigeria. Methods: A cross-sectional study was conducted, involving 265 men living in Ife Central who were married with at least one child, selected by multistage sampling. A structured questionnaire was used to assess men's knowledge of their expected roles in maternal healthcare, their perception of male involvement, and their current level of involvement in their spouse's healthcare. Descriptive and inferential statistical analyses were carried out to identify predictors of active male involvement in maternal healthcare, at a significance of P <0.05. Results: Approximately half (55.6%) of the respondents had good knowledge of the expected role of men in maternal healthcare services and 76.6% had a positive perception of this role. Overall, less than half (47.6%) of the participants were actively involved in maternal healthcare services. The participants most frequently reported that men's involvement was influenced by their degree of knowledge (92.4%), job schedule (92.0%), and clinic waiting time (86.4%), among others. Age (odds ratio=2.33, P =0.038), educational status (odds ratio=2.42, P =0.004) religion (odds ratio=2.34, P =0.012), occupation (odds ratio=2.81, P <0.001) and level of knowledge (odds ratio=2.34, P =0.001) were found to be significantly associated with men's level of involvement in maternal healthcare services. However, only good level of knowledge (adjusted odds ratio=2.32, P =0.004) emerged as an independent predictor of men's level of involvement in maternal healthcare services. Conclusions: The study concluded that men's involvement in maternal healthcare services was low, despite their positive perception towards it. Less than half of the participants had good knowledge regarding men's role in maternal healthcare, and this factor was identified as a significant predictor of level of involvement. Programmes and policies should aim to enhance men's knowledge of their role in maternal healthcare, and it may be necessary to restructure the healthcare delivery system to be more male friendly.